Predictive factors for recurrence in patients with Graves’ Disease following treatment with methimazole - Mohammad Robikhul Ikhsan; Raden Bowo Pramono; Hemi Sinorita; Vina Yanti Susanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Graves’ disease (GD) contributes for 60–80% of all hyperthyroidism. Methimazoleis the first line drug and most commonly used as antithyroid drug (ATD). However,the relapse rate following ATD therapy is 40–50%. The aimed of this studywas to evaluate long-term ATD treatments and to identify prognostic factorsthat contribute to GD recurrence. A total of 46 GD patients who referred to theEndocrinology Clinic, Dr. Sardjito General Hospital, Yogyakarta between January2016 and December 2018 with thyrotropin receptor antibody (TRAb) tested andtreated with methimazole were included in this study. Size of goiter was measuredbased on WHO grading system and eye syndrome based on NOSPEC score system.Patients were classified into recurrence and remission groups based on TRAbevaluation at 12 month following treatment. Result of thyroid hormone level (FT4)and subject characteristic as predictive factors observed at 3-, 6- and 12-month post-treatment were compared and analyzed.Among 46 patient involved in this study, 23patients demonstrated remission of hyperthyroidism based on TRAb evaluation at12-month. The size of thyroid at onset of disease in 30 (65%) patients was grade 2 orabove (p<0.05). Free FT4 levels at the end of observation (12 month) was 1.9±0.6 ng/dL in recurrent and 1.4±0.5 ng/dL in remission group (p<0.05). TRAb levels at earlyof study was higher in the recurrent group (p<0.05). Logistic regression analysisdemonstrated that thyroid size, FT4 level, and TRAb at diagnosis were associatedwith recurrencies. In conclusion, GD patients with large thyroids size, high TRAblevels, and high FT4 level at the onset of disease tended to fail to respond to ATD andwere associated with recurrence incidence.